SAT0676 Ultrasound detected inflammation in rheumatoid arthritis: elucidating the relationship with clinical manifestations at the wrist. (12th June 2018) - Tan, Y.K.; Moorakonda, R.B.; Allen, J.C.; Conaghan, P.G.; Chew, L.C.; Thumboo, J.
Abstract : Background: Tender and swollen joint counts are part of rheumatoid arthritis (RA) disease activity assessments. While subclinical synovitis is now a well-known entity, the relationship between tender and swollen joints and ultrasound (US) detected inflammation has not been well explored. Objectives: To compare US detected inflammation (synovitis and/or tenosynovitis) with joint swelling and/or tenderness of the wrist, an important joint in RA. Tendons are included as tenosynovitis on US can be mistaken for joint involvement clinically. Methods: Wrist outcome groups (Groups) 1–4 were identified: 1=S0 T0 (not swollen, not tender); 2=S0 T1 (not swollen but tender; 3=S1 T0 (swollen but not tender); 4=S1 T1 (swollen and tender). Power Doppler (PD) and grey-scale (GS) US were used to grade (a) synovitis semi-quantitatively (0–3) at the following joint recesses: dorsal radiocarpal and intercarpal, dorsal ulnocarpal and volar radiocarpal, and (b) tenosynovitis dichotomously (0=no, 1=yes) at the following tendon sites: extensor digitorum, extensor carpi ulnaris, and flexor digitorum. Scores on each wrist consisted of a PD score, a GS score and a combined (PD +GS) US (CUS) score. Positivity (+ve) for PD, GS and CUS scores was analysed using a generalised linear repeated measures mixed model with binary distribution and logit link. Scores were analysed using a general linear repeated measures mixed model assuming Gaussian errors. In both analyses, patients were modelled as random effects, and wrist (R/L) and follow up visit (baseline, 3 months) as fixed effects. Pairwise comparisons on +ve and scores were carried out among the 4 groups in the context of the models. P-values were not adjusted for multiple comparisons. Results: 122 wrist assessments resulted from 32 RA subjects (87.5% female; 78.1% Chinese; mean (SD) disease duration of 42.8 (52.9) months) who either started or escalated on systemic corticosteroids and DMARDs. All subjects were assessed at baseline and 29 at 3 months. Significant differences among Group scores were: 4 vs 1 (PD, p=0.0031; GS, p=0.0159; CUS, p=0.0045), 4 vs 2 (PD, p=0.0176; GS, p=0.0160; CUS, p=0.0074), and 4 vs 3 (CUS, p=0.0374). Significant differences among +ve were: 4 vs 1 (PD, p=0007), 4 vs 2 (PD, p=0.0234), and 3 vs 1 (PD, p=0.0202). No significant Group differences were found for 2 vs 1 (for +ve and scores) and when comparing the 4 groups for GS +ve and CUS +ve. Table 2 shows the frequency distribution of patients by wrist and follow up. There were no significant effects attributable to differences in wrists or follow up visit (p-values all >0.05). Disclosure of Interest: None declared